Lean six sigma approaches in manufacturing, services, and production - Tetteh, Edem, 1972-; Uzochukwu, Benedict M., 1962- (Research essentials., 2015)
"This book presents emerging research-based trends in the area of global quality lean six sigma networks and analysis through an interdisciplinary approach focusing on research, cases, and emerging technologies"--